1997
DOI: 10.1046/j.1570-7458.1997.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant structural complexity on the foraging success of Trichogramma minutum: a comparison of search on artificial and foliage models

Abstract: The influence of structural complexity on the foraging success for host eggs (Ephestia kuehniella Zeller) by Trichogramma minutum Riley was investigated in the laboratory. Naive females were released into arenas with structurally different paper models or foliage (simple: trembling aspen Populus tremuloides Michx., complex: balsam fir Abies balsamea L.). Observations of individual females were made every 15 min and searching success was measured by the number of host egg clusters found and the amount of time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…In the literature, structural complexity is recorded as affecting herbivores (Raghu et al, 2004;Rudgers & Whitney, 2006) and parasitoids (Andow & Prokrym, 1990;Lukianchuk & Smith, 1997). In several studies, host finding success of parasitoids is higher on simple structured plants than on those with complex structures (Andow & Prokrym, 1990;Lukianchuk & Smith, 1997;Gingras et al, 2002Gingras et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, structural complexity is recorded as affecting herbivores (Raghu et al, 2004;Rudgers & Whitney, 2006) and parasitoids (Andow & Prokrym, 1990;Lukianchuk & Smith, 1997). In several studies, host finding success of parasitoids is higher on simple structured plants than on those with complex structures (Andow & Prokrym, 1990;Lukianchuk & Smith, 1997;Gingras et al, 2002Gingras et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Structure can, however, also indirectly influence herbivorous insects via their natural enemies. At the scale of individual plants, Andow & Prokrym (1990) and Lukianchuk & Smith (1997) showed that a complex plant architecture not only reduces the probability of an egg parasitoid finding its hosts eggs, but also functionally reduces the parasitoids' searching time depending on the complexity of the plant. Gingras et al (2002) drew the same conclusions from a model of the influence of plant architecture on parasitism rate, which was validated in three natural tritrophic systems.…”
Section: Introductionmentioning
confidence: 99%
“…This contradicts the hypothesis that a complex vegetation structure provides a reduced risk of parasitism and that beetles should prefer to oviposit on host plants growing in dense vegetation (Andow & Prokrym, 1990;Gingras et al, 2002;Lukianchuk & Smith, 1997;Romeis et al, 2005).…”
Section: Top-down Effectsmentioning
confidence: 74%
“…"enemy-free space" (Jeffries & Lawton, 1984). It has been reported that a complex plant architecture has a negative effect on the searching efficiency of parasitoids (Andow & Prokrym, 1990;Gingras et al, 2002;Lukianchuk & Smith, 1997;Romeis et al, 2005). Additionally, Obermaier et al (2008) have shown that, in the tansy leaf beetle Galeruca tanaceti L. (Coleoptera: Chrysomelidae), high and dense vegetation close to the oviposition site had a negative effect on egg parasitism.…”
Section: Introductionmentioning
confidence: 99%
“…In these trials, two species of Trichogramma performed best at a smaller scale, while the third performed best at the largest spatial scale observed. Alternatively, multiple investigators have shown that habitat complexity affects Trichogramma foraging success in the laboratory (Andow and Prokrym 1990;Lukianchuk and Smith 1997;Gingras et al , 2003Andow and Olson 2003). Thus, it is possible that physical/structural homogeneity of the arenas used in this trial may have predisposed all three species to parasitize more hosts than when they were in a more heterogeneous habitat.…”
Section: Number Non-responding Females Treatmentmentioning
confidence: 99%